Development of Human Facial Expression Game for Autism Children Using Design Thinking Method - Haq, Yaritza; Ashar, Muhammad; Kirana, Kartika Candra (Universitas Negeri Malang, 2022)
Facial expression is one of the important factors in interacting and communicating activities. People can know the emotions and feelings of the interlocutor through their facial expressions. However, this can be difficult while doing interactions with children with autism. These limitations become obstacles in socializing for children with autism because not everyone can understand their feelings. To overcome this problem, a study was proposed with the title